Visual Snow: Visual Misperception. Issue 4 (December 2018) - White, Owen B.; Clough, Meaghan; McKendrick, Allison M.; Fielding, Joanne
Abstract : Background: Visual snow (VS) is a constant visual disturbance described as flickering dots occupying the entire visual field. Recently, it was characterized as the defining feature of a VS syndrome (VSS), which includes palinopsia, photophobia, photopsias, entoptic phenomena, nyctalopia, and tinnitus. Sixty percent of patients with VSS also experience migraine, with or without aura. This entity often is considered psychogenic in nature, to the detriment of the patient's best interests, but the high frequency of similar visual symptoms argues for an organic deficit. The purpose of this review is to clarify VSS as a true entity and elaborate the nature of individual symptoms and their relationship to each other. Evidence Acquisition: The literature was reviewed with specific regard to the clinical presentation and psychophysical, neurophysiological, and functional imaging studies in patients with defined visual disturbances that comprise VSS. Results: Consideration of the individual symptoms suggests that multiple factors are potentially involved in the development of VSS, including subcortical network malfunction and cortical hyperexcitation. Although there is substantial overlap between VSS and migraine syndromes in terms of co-occurring symptoms, both neurophysiological and neuroimaging studies provide substantial evidence of separate abnormalities of processing, supporting these as separate syndromes. Conclusions: VSS is likely associated with either hyperactive visual cortices or, alternatively, impaired processing of simultaneous afferent information projecting to cortex. VSS likely results from widespread disturbance of sensory processing resulting in sensory misperception. There may be a number of syndromes associated with impaired sensory processing resulting in sensory misperception, including migraine, persistent perceptual postural dizziness, and tinnitus, which overlap with VSS. Elucidation of abnormality in one defined syndrome may provide a path forward for investigating all.